An invitro study to Compare of shaping ability of tow preparation systems Reciproc blue with reciprocating movement and One curve with rotary movement According to maintenance of centering ratio and transportation of curved root canals (Journal of Hama University, 2022)
The study aimed to compare the ability to preserve the original shape of the canal (centering ratio and transportation of curved root canal ) for both of the two preparation systems that use only one file to prepare the root canals, such as the Reciproc blue with reciprocation motion and the one curve system with rotary movement on three levels of root canal.Methods and Materials:24 extracted human molar roots with a curvature that ranges between 25 and 60 degrees were selected. The sample was randomly divided into two groups N1 = N2 = 12. Both groups were manually prepared to # 15. Before the root canals of both groups were prepared with rotary systems to # 25. The sample was evaluated by A cone beam computed tomography (CBCT) before and after root canal preparation.Results:The results found that there was no significance difference between the two groups in terms of transporting and centering ratio of curve root canal. However, The Reciproc blue system was more conservative at the level of 3 and 9 mm and equal to the other at the level of 6 mm, but this difference was no significance (P>0.05). On the other hand, the one curve rotary movement system had less effect on the transportation on both levels 3 and 6 mm and more affected the 9 mm level. Also, this difference was no significance too (P>0.05).